A new approach in acute myeloid leukemia (AML): Samatya-predicting score. (2022) - Serin, Istemi; Orhan, Bagnu; Sonmez, Derya; Cinli, Tahir Alper; Goze, Hasan; Serin, Huriye; Gulesir, Begum; Yokus, Osman
Highlights: We aimed to examine the efficiency of our new scoring system in non-APL AML cases, . The AUC for the median risk score of 2, 5 in ROC analysis was 0, 635 ( p = 0, 006) for exitus; 0, 605 ( p = 0, 024) for being responder, . The sensitivity for mortality was 88%, the specificity 42%, the PPV 90, 1%, and the NPV was 24, 7%, . In terms of being non-responder to induction therapy, the sensitivity was 90, 1%, the specificity 25, 3%, the PPV 89, 8%, and the NPV was 32%. Abstract: We aimed to examine the efficiency for prediction of prognosis and response in non-APL AML cases of the "Samatya-predicting score". A total of 213 patients diagnosed between January 2010-December 2020 were examined. Of the 158 patients included in the study, the median value of risk score was determined as 2, 5. The sensitivity for mortality was 88% and the specificity was 42%. In terms of being non-responder to induction therapy, the sensitivity was 90, 1%, the specificity was 25, 3%. OS was shorter in those with high risk scores. This study makes an important contribution to the literature in terms of creating a different perspective to predict prognosis in AML.